Integration of Science in Contemporary Islamic Education: An Effort to Eliminate the Dichotomy Between Religious and General Knowledge - Haniefah Iqtianti; Melli Indah Novitasari; Muhammad Agung Prabowo; Muhammad Iqbal (JISEI: Journal of Islamic Studies and Educational Innovation, 2026)
Contemporary Islamic education currently faces the challenge of a dichotomy of knowledge, namely the separation between religious knowledge and general knowledge in the education system. This separation causes an imbalance in the character formation of students, where some students excel in knowledge but lack understanding of religion and morals, while others understand religion well but lack mastery of science and technology. This study aims to determine the concept of knowledge integration in contemporary Islamic education as an effort to eliminate the dichotomy between religious knowledge and general knowledge. This study uses a qualitative method with a library research approach. Data sources were obtained from books, scientific journals, articles, and various references relevant to the research theme. Data collection techniques were carried out through documentation and literature studies, while data analysis techniques used qualitative descriptive analysis. The results of the study indicate that knowledge integration in contemporary Islamic education is an effort to unite religious knowledge and general knowledge so that they run in balance. The concept of knowledge integration was developed through the thoughts of figures such as Syed Muhammad Naquib Al-Attas and Ismail Raji Al-Faruqi who emphasized the importance of the Islamization of knowledge. Furthermore, the integration-interconnection model (Spider Web) is also a form of scientific integration that connects various disciplines with Islamic values. The application of scientific integration in the Islamic Religious Education (PAI) curriculum can be achieved by linking religious material to real life, science, technology, and contextual learning. With this integration, students are expected to achieve a balance between intellectual, spiritual, and social abilities, thereby minimizing the dichotomy between religious and general knowledge in contemporary Islamic education.